Genome-wide study for circulating metabolites identifies 62 loci and reveals novel systemic effects of LPA - Johannes Kettunen (Nature Portfolio, 2016)
Circulating metabolites reflect human health and disease. Here, Kettunen et al. perform a genome-wide association study on 123 circulating metabolic traits and identify novel genetic loci influencing systemic metabolism. They also link new molecular pathways with a known cardiovascular risk factor Lp(a).